Transporting carriers for intracellular targeting delivery via non-endocytic uptake pathways - Zuhong Li; Yanhong Zhang; Danhua Zhu; Shuiqing Li; Xiaopeng Yu; Yalei Zhao; Xiaoxi Ouyang; Zhongyang Xie; Lanjuan Li (Taylor & Francis Group, 2017)
To develop novel therapies for clinical treatments, it increasingly depends on sophisticated delivery systems that facilitate the drugs entry into targeting cells. Profound understanding of cellular uptake routes for transporting carriers promotes the optimization of performance in drug delivery systems. Although endocytic pathway is the most important part of cellular uptake routes for many delivery systems, it suffers the trouble of enzymatic degradation of transporting carriers trapped in endosomes/lysosomes. Therefore, it is desirable to develop alternative transporting methods for delivery systems via non-endocytic pathways to achieve more effective intracellular delivery. In this review, we summarize the literature exploring transporting carriers that mediate intracellular delivery via non-endocytic pathways to present the current research status in this field. Cell-penetrating peptides, pH (low) insertion peptides, and nanoparticles are categorized to exhibit their ability to directly transport various cargos into cytoplasm via non-endocytic uptake in different cell lines. It is hoped that this review can spur the interesting on development of drug delivery systems via non-endocytic uptake pathway.